Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1001/jama.2021.1658
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination in Pregnant and Lactating Women

Abstract: Pregnant women with severe or critical coronavirus disease 2019 (COVID-19) infection are at increased risk for preterm birth and pregnancy loss. In studies of hospitalized pregnant women with COVID-19, which have included between 240 and 427 infected women, the risk for preterm delivery (both iatrogenic and spontaneous) has ranged from 10% to 25%, with rates as high as 60% among women with critical illness. 1 The primary risk to a pregnancy appears to be from maternal illness. In addition, pregnant women may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
98
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 8 publications
(16 reference statements)
0
98
0
2
Order By: Relevance
“…Our results provide information needed to inform the care of lactating individuals and their infants 12 . Although there is expert consensus of minimal or no potential risk for the infant from maternal anti-COVID-19 vaccination 13,14 , no previous studies have demonstrated specific benefits during lactation.…”
Section: Discussionmentioning
confidence: 86%
“…Our results provide information needed to inform the care of lactating individuals and their infants 12 . Although there is expert consensus of minimal or no potential risk for the infant from maternal anti-COVID-19 vaccination 13,14 , no previous studies have demonstrated specific benefits during lactation.…”
Section: Discussionmentioning
confidence: 86%
“…The vaccine campaign initially targeted high-risk populations (60 years old and healthcare providers) 2 and was soon expanded to lactating women 3 . Notwithstanding the reported high efficiency of this vaccine 4 and evidence for the generation of viral-specific antibodies in the breastmilk of women with COVID-19 [5][6][7] , there are no available data on its efficiency in lactating women or its potential benefits in neonatal protection via the passive transfer of vaccine-specific antibodies in breastmilk 8 . The current knowledge gap is preventing global health authorities from making concrete recommendations regarding vaccination during lactation.…”
mentioning
confidence: 99%
“…For example, healthcare workers and long term care residents receiving the first wave of vaccines in Phase 1a likely comprised a small fraction of the Phase 3 trial populations. Additionally, some pregnant women are receiving COVID-19 vaccines in the real world 12 , while they were excluded from both trials 4,5 . Finally, continuous monitoring will help to identify and better quantify the frequency of rare severe adverse effects such as anaphylaxis, which was widely reported but only observed in a small number of individuals after approval of both vaccines 13–17 .…”
Section: Introductionmentioning
confidence: 99%